Techniques for Mixed Multiple Shooting for solve Stiff Initial Value Problems - Khalid A. M. Khalaf; Bashir M. S. Khalaf (Tikrit Journal of Pure Science, 2023)
The object of the research is to develop a number of techniques on the subject of multiple shooting for solving stiff initial value problems, and these techniques increase the accuracy of numerical solutions of stiff problems, as well as reduce the accumulation of errors, In addition to reducing the algebraic equations to get to the solution. We used mixed-multiple shooting in the development of these techniques.